Petroclival Meningiomas: Factors Determining the Choice of Approach - Isolan, Gustavo Rassier; Wayhs, Sâmia Yasin; Lepski, Guilherme Alves; Dini, Leandro Infantini; Lavinsky, Joel (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives To review a surgical series of petroclival meningiomas and the factors considered in the choice of approach.Design Retrospective review.Setting The study was conducted in a university hospital in southern Brazil.Participants Twenty-two patients with petroclival meningioma originating from the upper two-thirds of the clivus medial to the fifth cranial nerve.Main Outcome Measures Gross-total resection, mortality, major morbidity, new cranial nerve deficits and tumor progression or recurrence.Results Retrosigmoid approach was used in tumors <3 cm and in those at or below the internal auditory meatus. Posterior petrosectomy was performed for tumors extending into the middle fossa. Gross-total resection was performed in 11 patients (50%). The mean follow-up time was 32 months (6–75 months). There were four cases of tumor progression or recurrence, which were treated with radiosurgery.Conclusions Resection of petroclival meningiomas remains challenging. In most cases, the retrosigmoid approach was sufficient, without affecting the degree of tumor resection. Petrosal approaches were reserved for patients with tumor extension into the middle fossa.
Keywords: brain tumor; clivus; meningioma; petroclival; skull base